#1**0 **

This isn't a "technical" proof, but let me give you an example that may help you to see why it's true.

Suppose we have (2^2)^3

What is this??

It's just (2*2) * (2*2) * (2*2). In other words, we're just "cubing" (2*2).

But, this is just 2 * 2 * 2 * 2 * 2 * 2 = 2^6 = 2^(2*3)

So, (2*2)^3 = 2^(2*3)

Does that help??

Suppose we have (2^2)^3

What is this??

It's just (2*2) * (2*2) * (2*2). In other words, we're just "cubing" (2*2).

But, this is just 2 * 2 * 2 * 2 * 2 * 2 = 2^6 = 2^(2*3)

So, (2*2)^3 = 2^(2*3)

Does that help??

CPhill Mar 16, 2014